Last updated at May 29, 2018 by Teachoo

Transcript

Ex 3.3, 23 Prove that tan 4 = (4 tan (1 tan2 ) )/(1 6 tan2 +tan4 ) Taking L.H.S. tan 4x = (2 tan 2x)/(1 tan2 2x) tan 4x = 2((2 tan )/(1 2 ))/(1 ((2 tan )/(1 2 ))^2 ) = (((4 tan )/(1 2 )))/(1 ((2 tan )^2/(1 2 )^2 ) ) = (((4 tan )/(1 2 )))/(1 ((4 ^2 )/(1 2 )^2 ) ) = (((4 tan )/(1 2 )))/((((1 2 )^2 4 ^2 )/(1 2 )^2 ) ) = (4 tan )/(1 tan2 ) ((1 tan2 )2 )/((1 2 )2 4 tan2 ) = (4 tan )/1 ((1 tan2 ) )/((1 2 )2 4 tan2 ) = (4 tan (1 2 ))/((1 tan2 )2 4 tan 2 ) Using (a b)2 = a2 +b2 2ab = (4 tan ( 1 tan2 ) )/(( (1)2+( 2 )2 2 1 2 ) 4 2 ) = (4 tan ( 1 tan2 ) )/(( (1)2+( 2 )2 2 1 2 ) 4 2 ) = (4 tan ( 1 tan2 ) )/(1 + tan 4 2 tan2 4 tan2 ) = (4 tan ( 1 tan2 ) )/(1 + tan4 6 4 ) = R.H.S. Hence L.H.S. = R.H.S. Hence proved

Ex 3.3

Ex 3.3, 1

Ex 3.3, 2 Important

Ex 3.3, 3 Important

Ex 3.3, 4

Ex 3.3, 5 Important

Ex 3.3, 6 Important

Ex 3.3, 7

Ex 3.3, 8 Important

Ex 3.3, 9 Important

Ex 3.3, 10

Ex 3.3, 11 Important

Ex 3.3, 12

Ex 3.3, 13

Ex 3.3, 14

Ex 3.3, 15

Ex 3.3, 16

Ex 3.3, 17

Ex 3.3, 18 Important

Ex 3.3, 19

Ex 3.3, 20

Ex 3.3, 21 Important

Ex 3.3, 22 Important

Ex 3.3, 23 Important You are here

Ex 3.3, 24

Ex 3.3, 25

Chapter 3 Class 11 Trigonometric Functions

Serial order wise

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 9 years. He provides courses for Maths and Science at Teachoo.